Assessing adequacy of informed consent for elective surgery by student‐administered interview. Issue 6 (14th May 2019) - Chia, Clement L. K.; Chan, Kai Siang; Ng, Marcus J. M.; Rao, Anil D.; Singaporewalla, Reyaz
Abstract : Background: Studies show that patients often sign consent documents without fully comprehending the risks, benefits and potential complications. There is currently no Asian study performed analysing adequacy of informed consent. This study aims to assess adequacy of informed consent by evaluating patient understanding and retention of key information and complications pertaining to surgery via medical student‐administered interview. Methods: A prospective study was performed on 48 patients undergoing groin hernia surgery, laparoscopic cholecystectomy and total thyroidectomy from 2017 to 2018 in a teaching hospital. Standardized assessment forms including major common complications and key details of the surgery were prepared. Structured one‐to‐one interviews between students and patients were performed and recorded on the morning of surgery. Results: Although 93.8% of the patients claimed to have understood the information regarding their surgery, only 19.4%, 44.4% and 62.5% of the patients could actually recall the serious complications of groin hernia surgery, laparoscopic cholecystectomy and thyroidectomy, respectively. Elderly patients (>65 years) had poorer understanding of surgical procedure compared to the young (80% versus 100%, respectively, P = 0.008) with 26.7% of elderly patients claiming that they did not understand the indication for surgery. High satisfaction rates with this preoperative interview were reported by both patients and students (95.8% and 97.9%, respectively). Time interval from informed consent to surgery did not make any difference. Conclusion: Understanding of information and key complications was generally low, especially in the elderly population. The structured preoperative interview achieved the dual goal of reinforcing patient gaps in knowledge and improving student communication skills.